A new inflammatory marker: elevated eosinophil-to-lymphocyte ratio associated with presence and severity of isolated coronary artery ectasia - Yilmaz, Mucahid; Kayancicek, Hidayet; Korkmaz, Hasan; Gozel, Nevzat; Bilen, Mehmet Nail; Secen, Ozlem; Ertugrul, Kurtoglu (Clinics Cardive Publ Pty Ltd, 2020)
Objectives: The pathophysiology of isolated coronary artery ectasia (CAE) involves atherosclerosis and inflammation. Eosinophils and lymphocytes have been found to play a significant role in inflanunation, atherosclerosis and endothelial dysfunction. Many studies have explored the relationship between isolated CAE and systemic inflammation. However, there are no data regarding the relationship between eosinophil-to-lymphocyte ratio (ELR) and isolated CAL Therefore, this study analysed the relationship between LER and isolated CAE. Methods: All patients who underwent coronary angiography between January 2009 and June 2018 were investigated retrospectively. Of 16 240 patients, 232 patients with isolated CAE (141 males) and 247 age- and gender-matched control subjects (130 males) with normal coronary angiography (NCA) were enrolled in this study. Baseline demographic and laboratory data were obtained from the hospital database. The severity of isolated CAE was determined according to the Markis classification, vessel count and diffuseness of ectasia. Results: Patients with angiographic isolated CAE had significantly elevated white blood cell (WBC) and eosinophil counts and ELR values compared to patients with NCA [8.11 +/- 1.75 vs 7.49 +/- 1.80 x 10(9) cells/l. p < 0.0001; 0.22 (0,13 0.32 vs 0.19 (0.12 0.28) x 10(9) cells/l, p = 0.02; 0.11 (0. 06-017) vs 0.08 (0.05-0.12), p < 0.0001. The ELR value for Markis I was significantly higher than for Markis IV (p = 0.04). and three-vessel isolated CAE was significantly higher than one-vessel isolated CAE (p = 0.04). Additionally. the ELR value for diffuse ectasia (Markis class I, II and III) was significantly higher compared to focal (Markis class IV) ectasia (p = 0.02). In receiver operating characteristics (ROC) analyses, it was determined that an EIR value > 0.099. measured in isolated CAF patients at application, had a predictive specificity of 60.3% and a sensitivity of 56.5% (area under the curve: 0.604, confidence interval: 0.553 0.655, p < 0.0001). Conclusion: Patients with isolated CAE had higher blood eosinophil counts and ELR. Furthermore. the ELR was significantly correlated with severity of isolated CAE These findings demonstrate that FLR may have a significant role in the aetiopathogenesis of isolated CAE.
Keywords: eosinophil count; eosinophil-to-lymphocyte ratio; isolated coronary artery ectasia; inflammation